The effect of anthropogenic features on the habitat selection of a large carnivore is conditional on sex and circadian period, suggesting a landscape of coexistence - Alegre, Vanesa Bejarano [UNESP]; Rio-Maior, Helena [UNESP]; Oshima, Júlia Emi de Faria [UNESP]; Niebuhr, Bernardo Brandão [UNESP]; Morato, Ronaldo G.; Ribeiro, Milton Cezar [UNESP] (Elsevier, 2023)
Improving coexistence between humans and large predators is one of the foremost issues for the survival of large carnivores, especially in the Neotropics, where conflicts for retaliation are still frequent. This problem was increased due to the expansion of agricultural areas, settlements, roads, and the loss of natural habitats. Therefore, a key component in the long-term conservation of carnivores is to reduce animal-human conflicts. We aimed to assess multi-scale habitat selection models, exploring specificities in the selection for each sex and variation for the circadian period. We found that jaguars live in real landscapes of fear with high human and livestock density, where the perception of risk related to humans governed the selection of their resources. However, depending on the sex of individuals and the circadian period, jaguars positively selected some anthropic structures, such as areas of crops and human settlements. This selection suggested an aptitude to use various human-dominated structures and indicated jaguars could locally perceive risks in different ways, depending of sex and day period. Unexpectedly, jaguars presented attraction to roads, sexual or circadian related, regardless of the natural environments. Our results demonstrate that male and female jaguars could use some anthropic features differently in the distinct circadian periods. In addition, we conclude that the knowledge of the habitat selection for jaguars is a crucial component to the structure of the landscape of coexistence of this species and can give us efficient guidance to better comprehend the behavior through different scales of selection and through different periods of the day. Finally, our results show fundamental observations on the movement plasticity of this species for the construction of conservation plans focusing on the coexistence in different landscapes of the Neotropics dominated by humans.